Development of a reliable and valid kata performance analysis template - Augustovicova. D.; Argajova, J.; Rupcik, L.; Thomson, E. (Journal of Physical Education and Sport, 2020)
With the new kata evaluation procedure, examination of the underpinning features of successful kata performance appears warranted. The purpose of the study was to create a valid and reliable analysis template for the assessment of the movement characteristics of competitive kata. Following the creation, and scrutiny, of action variables and operational definitions, three observers were provided with the operational definitions of the performance indicators, example kata clips and instructions detailing the method of `tagging` using a computerized analysis software. Intra- and inter-rater reliability assessment and median sign tests, and Cohen`s Kappa coefficient were conducted. There were no significant differences (p ? 0.05) between the observer`s and analyst`s test-retest observations for all the performance indicators. The intra-rater reliability was found to be "almost perfect" in all raters (LA K = 0.99 [95% CI: 0.98-0.99]; PA K = 0.94 [95% CI: 0.93-0.95]; KR K = 0.94 [95% CI: 0.93-0.95]) and the inter-rater Kappa coefficients were moderate (K = 0.55 ± 0.05). This study has demonstrated that a novel performance analysis template yields reliable observations of the key movements during kata and the procedures couldtherefore be used to objectively appraise features of successfulperformance.